The Relation between Pediatric Immunodeficiency Category and Diarrhea in AIDS/HIV Infected Child - Satrio Wibowo (Universitas Airlangga, 2012)
Introduction: Diarrhea is one of the most prevalent cause of mortality and morbidity in AIDS/HIV infected child. Severe immune suppression increase prolong and persistent diarrhea. The correlation between diarrhea and immune suppression level has not well known yet, particularly in Saiful Anwar Hospital. The aim of this study is to determine relation between immune suppression leveland prolonged or persistent diarrhea in AIDS/HIV infected child.Method: Retrospective crosssectional research were conducted on 68 medical records taken from patients who were admitted between February 2008 and August 2011. The characteristic of data taken were: age, sex, nutritional status, CD4+ counts, duration of diarrhea, other comorbid diseases beside diarrhea (pneumonia, tuberculosis, moniliasis) and the patient outcome. National Guidelines Clinical Management of HIV/AIDS in Children were used to diagnose HIV/AIDS. Immune supression level was determined using CDC guidelines. Immune supression level was ranked in to four categories: no immune deﬁcient, mild suppression, moderate suppression, and severe immunodeﬁcient.Result: Thirty six (53%) patients were male; diarrhea was found in 32 (47%) patients, acute diarhhea in 12 patients, prolonged diarrhea in 1 patient, persistent diarrhea in 19 patients. Forty (40%) were severe immunodeﬁcient, 6% mild, 28% moderate and 40% without immunodeﬁ ciency.Discussion: Statistical analysis showed that there was no correlation between immune supression level and types of diarrhea. (95% CI, p = 0.17).